A constituição da docência de professores universitários do Curso de Bacharelado em Enfermagem de uma Instituição de Ensino Superior - Lemos, Dalila Marques (2021)
Teaching has been studied from different perspectives interested in understanding “being a teacher” and all the interactions that result from it. This research aims to understand the constitution of the teaching of professors in the Bachelor of Nursing course at a public institution. This work integrates studies on teacher training and educational practices, namely research line 1 of the Graduate Program in Education at the Federal University of Roraima (PPGE/UFRR). It is a qualitative study with Participant Research characteristics. The research subjects were 10 university professors from the undergraduate nursing course at a Brazilian university located in the northern region. As a data collection technique, we used the application of a questionnaire and semi-structured interviews whose data were analyzed using Bardin's Content Analysis (2016). Specifically, this research dealt with knowing the teaching knowledge in the area of nursing education; present the personal and professional trajectory of teachers and; identify the meaning given to pedagogical knowledge in nursing teaching. For this, it was necessary to carry out a literature review in order to know investigations about the central theme. A state of knowledge of a bibliographic base was also elaborated, with a quantitative-qualitative approach, developed to know the Brazilian scientific production on the constitution of nursing teaching in the last twenty years (2001-2020). In general, the main finding of this stage of the present research was evidenced, namely: the constitution of teaching and, specifically, teaching in nursing is dynamic and diversified since the works were about professional training and development, theory and practice, teaching in public and private sector institutions, educational policies, precariousness and conditions of teaching work, and building skills. In this sense, we decided to categorize the results of the interview conducted with the participants into 03 main thematic lines, each one composed of 03 subcategories: teaching paths in Nursing education – trajectories and practical complementation of care; teaching knowledge in nursing education and; challenges and hopes of university teaching in nursing. The teaching perspective was being cultivated in life experiences: growth within the school environment, study group, family members who are teachers, family members who are nurses, interaction with health professionals, political engagement that leads to inclusion, a minority. However, pedagogical knowledge is not so present in formal education at undergraduate and graduate levels. When asked about class narratives, participants raised questions concerning feelings such as insecurity, shyness, inquisitive student profile; need for professional care practice as a possibility to complement what is taught in the classroom; existence of fragmentation between the position of professor and professional nurse.